THE DEVELOPMENT OF PARENTING MODULE "PLAYING MENU WITH PARENT" TO IMPROVE CHILDREN’S PROSOCIAL BEHAVIOUR - Euis Nurfaridah; Agus Hasbi Noor; Ansori Ansori (Journal Of Educational Experts (JEE), 2021)
The purpose of this study is to ascertain the development of parenting modules "Play Menu with Parent" for the purpose of fostering early childhood prosocial behavior skills and the efficacy of the parenting module The purpose of this research is to develop a parenting module titled "Playing Menu with Parent" and to determine its efficacy in developing prosocial behavior in young children. The process of development entails planning, design, and implementation. Product validation is carried out by material and media experts who provide feedback and assessments on the products developed. Following that, small-scale trials using a revised product design were conducted. Prior to use in large-scale trials, product revisions are performed. Additionally, researchers elicit parental feedback and suggestions for improvement to serve as a guide for revising the product before it becomes the final product. The findings indicated that the developed products are deserving of being used by parents as a self-learning medium. This is based on expert validation of the material, which achieved an 86 percent level of validity. A validity rate of 62% was achieved by media experts. Peers estimate a valid rate of 90 percent. Educators demonstrated a 91 percent validity rate. This demonstrates the utility of the parental module. Observations of parental parenting activities revealed that an astounding 88 percent of them fell into the extremely high category. Additionally, parents receive an average score of 51.9 on the pretest and a score of 86.4 on the posttest. The t-test resulted in a t-count of 15.43 and a table length of 1.725, indicating that t-count>ttabel. These findings indicated that there were significant differences between the pre- and post-usage of the parenting module "Playing Menu with Parent." As a result, it can be concluded that the modules developed are effective at fostering prosocial behavior in young children.